INTEGRATED MARKETING STRATEGY FOR BEVERAGES FRANCHISE INDUSTRY - Mohammad Hamim Sultoni (JURNAL MAKRO MANAJEMEN, 2019)
Trend of food and beverage industry in Asian market shows a positive growth. it is showed that nominal growth in the region over the next five years is expected to average 9% per year compared to a global average of 6.4% per year. Cokelat Klasik as a business in the F&B line optimistic to fight in the market and competition. For over eight-monthsoperation, Cokelat Klasik has a main hypothesis problem about the unreached target sales. According to the data, percentage of reachable target sales of Cokelat Klasik is 54% and is still unreached target sales. So, this research have goals to know the effectivemarketing strategy that’s can be implemented for the next step. The approach used is qualitative methods. The depth-interview will be primary data to collect information from external environment. Then, literature review is also used to support analysis as secondary data. Internal data will be analyzed using Business Model Canvas, 4Ps Analysis, STP (Segmenting, Targeting, and Positioning) and Strength & Weakness. External data will be analyzed using the Porter Five Forces, Competitor Analysis and Opportunity & Threat. Then, the internal data and external data will be analyzed in TOWS Matrix. The proposed solution is derived from the new marketing mix and Program of Integrated Marketing Communications (IMC). The element of IMC that’s used is consist ofsix tools, which are: advertising, sales promotion, event and sponsorship, directmarketing, and digital/internet marketing. The implementation plan is set on one year periods which is from Sept 2017 until August 2018.